Rifaximin in the treatment of hepatic encephalopathy - Iadevaia MD (Dove Medical Press, 2011)
Maddalena Diana Iadevaia, Anna Del Prete, Claudia Cesaro, Laura Gaeta, Claudio Zulli, Carmelina LoguercioDepartment of Internistica Clinica e Sperimentale, F Magrassi e A Lanzara, Hepatogastroenterology Unit, Second University of Naples, Naples, ItalyAbstract: Hepatic encephalopathy is a challenging complication in patients with advanced liver disease. It can be defined as a neuropsychiatric syndrome caused by portosystemic venous shunting, ranging from minimal to overt hepatic encephalopathy or coma. Its pathophysiology is still unclear, although increased levels of ammonia play a key role. Diagnosis of hepatic encephalopathy is currently based on specific tests evaluating the neuropsychiatric state of patients and their quality of life; the severity of hepatic encephalopathy is measured by the West Haven criteria. Treatment of hepatic encephalopathy consists of pharmacological and corrective measures, as well as nutritional interventions. Rifaximin received approval for the treatment of hepatic encephalopathy in 2010 because of its few side effects and pharmacological benefits. The aim of this work is to review the use and efficacy of rifaximin both in acute and long-term management of hepatic encephalopathy. Treatment of overt hepatic encephalopathy involves management of the acute episode as well as maintenance of remission in those patients who have previously experienced an episode, in order to improve their quality of life. The positive effect of rifaximin in reducing health care costs is also discussed.Keywords: acute hepatic encephalopathy, recurrent hepatic encephalopathy, rifaximin, lactulose, cost, health-related quality of life